Exploring The Main Factors Influencing Stock Price Volatility in China Based on The GARCH-MIDAS Model - Li, Jia-Cheng; Yoon , Seong-Min (NIDA Development Journal, 2024)
This article comprehensively explores factors that affect stock price fluctuations from three perspectives: geopolitical events, economic indicators, and financial factors.In order to analyze these influences, we used data from July 1997 to February 2023 and employed the GARCH-MIDAS model with the Shanghai Composite Index variable for empirical analysis. The main findings of this study are summarized as follows. Firstly, the Chinese Investors’ Confidence Index, Consumer confidence index, Entrepreneur Confidence Index, Housing starts, Default Spread, and Industrial Added Value positively impact long-term stock market volatility. This effect gradually strengthens over time. Other variables hurt the long-term volatility of the stock market. Secondly, Default Spread has the highest predictive power, followed by USDX and Retail of Consumer Goods. Thirdly, the impact of geopolitical events, economic indicators, and financial factors on stock market fluctuations varies significantly.